DAMPAK INOVATION CAPABILITY TERHADAP COFFEE SHOPS COMPETITIVENESS DI KOTA BANJARMASIN - Gea Hiqori Sonia; Zakhyadi Ariffin; Editor, admin (JWM (JURNAL WAWASAN MANAJEMEN), 2023)
Coffee shops are a trending business in Indonesia, including in the city of Banjarmasin. Although many coffee shops have been established, however many coffe shops have failed. Competitiveness determines the success of a coffee shop in intensive competition. Purpose. The purpose of this study was to investigate the effect of market orientation and entrepreneurial orientation on competitiveness mediated by organizational innovation.Methods The research was conducted on the coffee shop industry in the city of Banjarmasin which is not a franchise. Questionnaires were sent to 50 coffee shops registered with the Banjarmasin city government. A total of 40 coffee shop managers answered the questionnaire. Data analysis uses partial least squares (PLS). Result. The results of the study show that market orientation and entrepreneurial orientation have a direct effect on competitiveness. Organizational innovation can mediate the effect of market orientation and entrepreneurial orientation on competitiveness